Capabilities and limitations of using DNA metabarcoding to study plant–pollinator interactions. Issue 20 (29th August 2021) - Arstingstall, Katherine A.; DeBano, Sandra J.; Li, Xiaoping; Wooster, David E.; Rowland, Mary M.; Burrows, Skyler; Frost, Kenneth
Abstract: Many pollinator populations are experiencing declines, emphasizing the need for a better understanding of the complex relationship between bees and flowering plants. Using DNA metabarcoding to describe plant–pollinator interactions eliminates many challenges associated with traditional methods and has the potential to reveal a more comprehensive understanding of foraging behaviour and pollinator life history. Here we use DNA metabarcoding of ITS2 and rbcL gene regions to identify plant species present in pollen loads of 404 bees from three habitats in eastern Oregon. Our specific objectives were to (i) determine whether plant species identified using DNA metabarcoding are consistent with plant species identified using observations, (ii) compare characterizations of diet breadth derived from foraging observations to those based on plant species assignments obtained using DNA metabarcoding, and (iii) compare plant species assignments produced by DNA metabarcoding using a "regional" reference database to those produced using a "local" database. At the three locations, 31%–86% of foraging observations were consistent with DNA metabarcoding data, 8%–50% of diet breadth characterizations based on observations differed from those based on DNA metabarcoding data, and 22%–25% of plant species detected using the regional database were not known to occur in the study area in question. Plant–pollinator networks produced from DNA metabarcoding data had higher sampling completeness and significantly lower specialization than networks based on observations. Here, we examine some strengths and limitations of using DNA metabarcoding to identify plant species present in bee pollen loads, make ecological inferences about foraging behaviour and provide guidance for future research.